Heartburn [compact disc, unabridged] - Ephron, Nora (Books On Tape : Random House Audio, 2013)
Seven months into her pregnancy, Rachel Samstat discovers that her husband, Mark, is in love with another woman. The fact that the other woman has a neck as long as an arm and a nose as long as a thumb is no consolation. Food sometimes is, though, since Rachel writes cookbooks for a living. And in between trying to win Mark back and loudly wishing him dead, Ephron's irrepressible heroine offers some of her favorite recipes.